The relationship between the quality of fiber in coats and the service rendered - Hunter, Bertha Viola, author; Dyar, Elizabeth, advisor; Allison, Inga M. K., committee member; Bertone, Eugene B. (Eugene Bruno), committee member (Colorado State University. Libraries, 1944)
To view the abstract, please see the full text of the document.
Keywords: Clothing and dress; Coats